2021
DOI: 10.1021/acs.jafc.1c04370
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Bioactivity, Toxicity, and Degradation in Vegetables and Soil of Chiral Fungicide Mandipropamid

Abstract: Mandipropamid (MDP) is a widely used chiral fungicide to control oomycete pathogens with two enantiomers. In this study, the enantioselective bioactivity, toxicity, and degradation of MDP were investigated for the first time. The bioactivity of S-MDP was 118–592 times higher than that of R-MDP and 1.14–1.67 times higher than that of Rac-MDP against six phytopathogens. Molecular docking found that S-MDP formed a strong halogen bond with HIS 693 of cellulose synthase and possessed a lower binding energy, which v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…An EF value of 0.5 indicates no enantioselectivity. Moreover, the S -enantiomer is preferentially removed for EF values in the range of 0.5–1 [ 21 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…An EF value of 0.5 indicates no enantioselectivity. Moreover, the S -enantiomer is preferentially removed for EF values in the range of 0.5–1 [ 21 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…13 The bioactivity of Smandipropamid was 118−592 times greater than that of Rmandipropamid against six plant pathogens. 14 S-Triticonazole had greater acute toxicity to non-target aquatic and terrestrial organisms. 15 The toxicity of R-oxathiapiprolin to aquatic plants and zebrafish was higher than that of S-oxathiapiprolin, 16 and R-oxathiapiprolin had greater distribution in animal tissue (liver and lungs).…”
Section: ■ Introductionmentioning
confidence: 96%
“…Based on the supercritical fluid chromatography-tandem mass spectrometry method, S -diniconazole was preferentially degraded in fruits . The bioactivity of S -mandipropamid was 118–592 times greater than that of R -mandipropamid against six plant pathogens .…”
Section: Introductionmentioning
confidence: 99%
“…10−14 Research groups such as Zhang et al compared the enantioselective bioactivity against six phytopathogens, the toxicity in the Danio rerio embryo and larva, and the degradation in cowpea, pepper, and soil of the chiral fungicide Mandipropamid, and the results revealed that the development of the S-enantiomer would be considered as a better option to exhibit high efficiency, which could reduce the residual risk of the pesticide and ensure environmental safety. 15 Therefore, it is essential to study the enantioselective bioeffects and environmental behaviors of chiral pesticides at the enantiomer level to obtain more accurate data. The enantiomer of chiral pesticides could be more effective against insects and less toxic to nontarget organisms and so would improve the food safety and reduce environmental risks.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in the awareness of food safety and human health, more and more researchers have begun to pay much attention to chiral pesticides for the assessment of a possible replacement of commercial racemate with a single stereoisomer. It has been reported that the chiral pesticide enantiomers that had identical physicochemical properties showed enantioselectivity in biological activity, dissipation behavior, bioaccumulation, transformation, and biological metabolism when they were introduced to a chiral environment. Moreover, a significantly different toxicity effect of chiral pesticide enantiomers is also often exhibited in cancer promotion, cytotoxicity, and endocrine disruption to nontarget biota. Research groups such as Zhang et al compared the enantioselective bioactivity against six phytopathogens, the toxicity in the Danio rerio embryo and larva, and the degradation in cowpea, pepper, and soil of the chiral fungicide Mandipropamid, and the results revealed that the development of the S -enantiomer would be considered as a better option to exhibit high efficiency, which could reduce the residual risk of the pesticide and ensure environmental safety . Therefore, it is essential to study the enantioselective bioeffects and environmental behaviors of chiral pesticides at the enantiomer level to obtain more accurate data.…”
Section: Introductionmentioning
confidence: 99%